Short report on the archaeological research of the burial mounds no. 64. and no. 49 of Érd- Százhalombatta - Németh, Gabriella T.; Czajlik, Zoltán; Novinszki-Groma, Katalin; Jáky, András (Dissertationes Archaeologicae, 2017)
x